Potensi Wisata Edukasi Berbasis Wisata Ramah Anak di Daya Tarik Wisata Desa Coklat Bali Tabanan - Dian Pramita Sugiarti; I Gusti Agung Oka Mahagangga; Krista S. Romer; Komang Kesya Amanda Paramitha (JURNAL DESTINASI PARIWISATA, 2022)
The condition of Bali tourism during the Covid-19 pandemic has become very concerning, on the one hand, the need fortravel is very high but cannot be balanced with the fact of the opening and closing of tourist destinations. Some of thetourist destinations that were closed were used as an opportunity for managers to renovate managed tourist destinationsto comply with CHSE standards. The current conditions have also provided new lessons for managers and touristsregarding the safety of traveling during a pandemic. Special interest tourism such as educational tours is currently indemand by family tourists who want to spend time with family and learn about the culture of local people. Bali ChocolateVillage is Chocolate Village is a new tourist destination in Bali since October 2020. It is located in Cau Village, MargaDistrict, Tabanan Regency. The founder of Chocolate Village is Dr. Ir. I Wayan Alit Artha Wiguna, M.Si. who built the touristattraction of Chocolate Village. Chocolate Village began to be known for educational tours that can provide insight forchild tourists about how the process of growing chocolate fruit to the process of making it. Chocolate Village is a favoritedestination today by local tourists and residents. The founder of Chocolate Village is I Wayan Alit Artha Wiguna who wantsto provide new educational tours for child tourists to learn new lessons about the chocolate-making process and educatetourists so that they get to know the chocolate tree which is one of the plantation plants in Indonesia. This child-friendlytourism-based educational tour is expected to: 1) Become a pilot for child-friendly tourist attractions. 2) Promote childfriendlybased educational tourism in every attraction of educational tours. 3) There is a change in the perspective ofvisitors related to the benefits of educational tourism activities.The formulation of the problems to be raised is 1) The potential of Bali Chocolate Village as a child-friendly tourismbasededucational tour 2) the existing condition of Bali Chocolate Village as a tour Child-Friendly Travel-Based EducationData were collected by observation, in-depth interviews, dissemination of questionnaires, literature studies, anddocumentation techniques. Data analysis techniques use descriptive qualitative and SWOT. The results of the identificationof educational tourism are expected to be able to provide new knowledge in traveling, educational tourism activities canstimulate interest and creativity in children, increase children's motivation Amid a period of school saturation from home,increase the attitude of respect and care for the tourist destinations visited such as natural tourism by protecting theenvironment and forming closeness between families.Keywords: Bali Chocolate Village, Child-Friendly Tourism, Educational Tourism